2016
DOI: 10.1097/nmd.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Meaning in Life and Values in Patients With Severe Mental Disorders

Abstract: Spirituality and meaning in life are key dimensions of recovery in psychiatric disorders. The aim of this study was to explore spiritual meaning in life in relation to values and mental health among 175 patients with schizophrenia, borderline personality disorder, bipolar disorder, and anorexia nervosa. For 26% of the patients, spirituality was essential in providing meaning in life. Depending on the diagnosis, considering spirituality as essential in life was associated with better social functioning; self-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…However, about one-third of participants with religious experiences kept their distance from such experiences or were uncertain whether they were authentic or belonged to BD. Huguelet et al (2016) assessed the subjective importance of religion and spirituality and found a much higher prevalence of what they called 'essential spirituality' in the patient group with a diagnosis of schizophrenia (41%) compared to BD (6%). Measured in their study was religious affiliation, private/public practice, importance in daily life, and religion or spirituality as a provider of meaning to life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, about one-third of participants with religious experiences kept their distance from such experiences or were uncertain whether they were authentic or belonged to BD. Huguelet et al (2016) assessed the subjective importance of religion and spirituality and found a much higher prevalence of what they called 'essential spirituality' in the patient group with a diagnosis of schizophrenia (41%) compared to BD (6%). Measured in their study was religious affiliation, private/public practice, importance in daily life, and religion or spirituality as a provider of meaning to life.…”
Section: Discussionmentioning
confidence: 99%
“…Religion has been reported to play an important role in coping with serious mental illness and can serve as a positive source for recovery for many patients with such a condition (Huguelet et al 2016;Koenig 2009;Mohr et al 2012). Religion is likely to sustain hope, a positive sense of self, comfort, meaning of life, enjoyment of life, love, and compassion (Mohr et al 2006).…”
Section: Religion and Serious Mental Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that one source of support for help-seekers is the church, a physical location and social group who can be depended upon for support and a set of practices that provide meaning. 49 In contrast, the psychics had a metaphysical account of their voices, less constrained by doctrine and therefore, perhaps more accommodating of their specific circumstances and experiences. This group may have relied less on communal organization because of their differences in belief, although it should be noted that some psychics did have spiritual organizations to which they belonged in which they often found comfort (see individual quotations in table 4 for instances of this).…”
Section: Discussionmentioning
confidence: 99%
“…This includes spiritual issues in general, eg. finding meaning and purpose in life, ("existential"), (Galanter et al, 2011, Huguelet, 2016, and a religious faith in particular, (Borras et al, 2007, Mohr et al, 2012. Clinicians often find these issues difficult to address, (Borras et al, 2010).…”
Section: Introductionmentioning
confidence: 99%